Persepsi Perkuliahan Al-Islam dan Kemuhammadiyahan (AIK) Bagi Mahasiswa Non Muhammadiyah di PTMA - Nusaibah, Afaf Wafiqoh; Arqam, Muhammad Lailan; Tamam, Badru (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2024)
Perception of Al-Islam and Muhammadiyah lectures for non-Muhammadiyah students as a course. The aim of this research is to find out students' knowledge regarding Al-Islam and Muhammadiyah lectures, do non-Muhammadiyah students feel they understand the lectures given or vice versa? To find out whether in attending Al-Islam and Muhammadiyah lectures non-Muhammadiyah students really internalize it or even just as a formality? This research approach uses qualitative research. Meanwhile, data collection in this research uses the interview method. The findings from this research are that after attending AIK lectures, non-Muhammadiyah students have increased understanding. The majority of non-Muhammadiyah students after attending AIK lectures did not change their previous attitudes or understanding. So most non-Muhammadiyah students consider AIK lectures to be just an academic formality.